Acoustical Evaluation of High-School Technology-Education Shops. Issue 1 (March 2015) - Summan, Ahmed; Hodgson, Murray
This study investigated the acoustical conditions in high-school Technology-Education Shops (TES) and the conflict that may exist due to their use at the same time as classrooms for learning and as industrial workshops for fabrication. This was done by measuring relevant acoustical characteristics in twenty TES in British Columbia when unoccupied with building services operating, and in ten of them when occupied and in normal operation with shop equipment running. The results were compared to existing acceptability/design criteria for classrooms and industrial workshops, related to background-noise level, teacher noise exposure, reverberation time, speech-intelligibility index (SII) and sound-level reduction with distance doubling (DL2 ), and pass/fail ratings were assigned. Noise levels and reverberation times in most unoccupied TES were higher than the acceptability/design criteria for core learning spaces. Teacher daily noise exposures in occupied TES were high and often exceeded regulatory limits. SII values often indicated 'poor' speech intelligibility for 'normal' and 'raised' vocal outputs, and 'good' speech intelligibility only for 'loud' and 'shout' vocal outputs. DL2 values were unacceptable in most of the TES. Most TES received a failing grade with respect to most evaluation criteria. The results confirm the existence of an acoustical conflict; the acoustical conditions in the TES as industrial rooms are generally unsatisfactory for their use as classrooms. In general, the results suggest that TES provide poor acoustical conditions, overexposing teachers and students to noise, and are in need of effective sound-design and noise-control measures.